Saltwater : a novel - Hays, Katy, 1982- (Ballantine Books, 2025)
"From New York Times bestselling author of The Cloisters comes an electrifying thriller about an opulent family and their mysterious assistant whose annual retreat to Italy is shattered by the resurfacing of a decades-old murder. The world was shocked by playwright Sarah Lingate's death thirty years ago at a Moorish, whitewashed villa on the island of Capri. Absolved of the crime, the Lingate family maintains that what happened that night was a tragic accident, and every July they come back to prove it's true. This time, Helen Lingate, sole heir to the family fortune, has a plan. Tightly controlled by her father, Helen enlists the help of the family assistant, Lorna Silva, to free herself from her family's grip. But behind closed doors, the legendary Lingate family unity is at a breaking point. Upon arrival to their villa in Capri, a gift is waiting for them: the necklace Sarah was wearing the night she died. In the aftermath, the paranoid, insular Lingates begin to unravel. As the investigation into her mother's death is reopened, Helen begins to lose trust in everyone around her: her controlling father Richard, drug-addled aunt Naomi, aloof uncle Marcus, and even Lorna, whose past she realizes is frustratingly opaque. And as they fracture, the long-hidden truth about that night and the secrets they've kept from one another boil to the surface-and they might not leave the island alive. On glittering Capri, anything can be a mirage. And one thing is true: no one holds a grudge like family"--